2013
DOI: 10.1371/journal.pone.0075103
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Alpha Toxin Suppresses Effective Innate and Adaptive Immune Responses in a Murine Dermonecrosis Model

Abstract: An optimal host response against Staphylococcus aureus skin and soft tissue infections (SSTI) is dependent on IL-1β and IL-17 mediated abscess formation. Alpha toxin (AT), an essential virulence factor for SSTI, has been reported to damage tissue integrity; however its effect on the immune response has not been investigated. Here, we demonstrate that infection with USA300 AT isogenic mutant (Δhla), or passive immunization with an AT neutralizing mAb, 2A3, 24 h prior to infection with wild type USA300 (WT), res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
83
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 52 publications
14
83
0
1
Order By: Relevance
“…3A) and dermonecrotic skin lesion area (Fig. 3B) compared to WT S. aureus, consistent with previously reported observations (15,21,28,42). S. aureus recovery (CFU) from skin abscesses was similar among all three strains at the 30-h time point (Fig.…”
Section: Psm Expression Regulates Hla Production In Vitrosupporting
confidence: 91%
See 1 more Smart Citation
“…3A) and dermonecrotic skin lesion area (Fig. 3B) compared to WT S. aureus, consistent with previously reported observations (15,21,28,42). S. aureus recovery (CFU) from skin abscesses was similar among all three strains at the 30-h time point (Fig.…”
Section: Psm Expression Regulates Hla Production In Vitrosupporting
confidence: 91%
“…The observed reduction in Hla expression by psm mutant strains in vitro suggested that the attenuated dermonecrosis phenotype observed upon skin infection with the S. aureus ⌬psm␣ psm␤ hld strain was potentially attributable to the loss of Hla activity. In murine and rabbit model systems, disruption of Hla expression or receptor availability results in a moderate reduction in overall skin abscess size but a near-complete attenuation of epidermal injury, corresponding to the maintenance of E-cadherin-based intercellular adherens junctions (15,21,24,42). To determine whether psm loci have a regulatory effect on Hla production in vivo, we performed a comparative analysis of Hla Ϫ and PSM Ϫ strains in the skin and soft tissue model of infection.…”
Section: Psm Expression Regulates Hla Production In Vitromentioning
confidence: 99%
“…We previously reported on the prophylactic efficacy and mechanism of action of an anti-AT MAb, 2A3, in the murine dermonecrosis model (9,18). To assess the potential of an AT-neutralizing MAb as a therapeutic for S. aureus skin and soft tissue infections, the therapeutic activity of LC10 (MEDI4893*), an affinity-optimized version of 2A3 (13), was compared with those of two frontline antibiotics, vancomycin and linezolid, in the murine dermonecrosis model.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-toxin (AT), a 33-kDa cytolytic pore-forming toxin produced by a majority of S. aureus clinical isolates, has been reported to blunt this protective immune response. In a dermonecrosis model, it has been demonstrated that mice infected with S. aureus isogenic mutants defective for AT expression mount a robust inflammatory cytokine response (e.g., IL-1␤, keratinocyte chemoattractant [KC], IL-6, and IL-17) with accompanying immune cell infiltration, abscess formation, and significant disease attenuation compared to the case for mice infected with wild-type S. aureus (9,10). We reported similar results following prophylactic administration of the AT-neutralizing monoclonal antibody (MAb) 2A3, the MEDI4893* precursor (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation